Effect of cytokinin on morphological and physiological characteristics and antioxidant enzymes activity of aged groundnut (Arachis hypogaea L.) seeds under drought stress - A. Sepehri; H.R. Rouhi (علوم و فناوری بذر ایران)
In order to investigate the effect of cytokinin on improvement of aged groundnut seeds under drought stress, a factorial experiment was done based on completely randomized design with three replications. Seed priming with different concentrations of cytokinin including 0 (hydropriming), 50, 100 and 150 ppm in drought stress levels (0, -0.4, -0.6 and -0.8 MPa) was performed. Germination percentage, mean germination time, germination rate, seed vigor, seedling length, soluble carbohydrates, soluble proteins, memberane electrical conductivity, malondialdehyde content and antioxidant enzymes activity (catalase, ascorbate peroxidase and superoxide dismutase) were evaluated. The results showed that seed priming with different concentrations of cytokinin alleviated significant decrease of germination and seedling parameters of aged seeds under drought stress. At -0.8 MPa, seed priming with 100 ppm of cytokinin increased germination percentage, vigor index , soluble carbohydrates and proteins 0.65, 1.73, 1.09, 1.05, and in 150 ppm of cytokinin 1.37, 4.51, 2.5, 2.85 fold, as well as the activity of catalase, superoxide dismutase and ascorbate peroxidase increased by 15.92, 13.35, 33.17 and 25.47, 17.96, 45.19% in comparison to control, respectively. Therefore, cytokinin pre-treatment specialy with 150 ppm is effective in germination and seedling indices of aged groundnut seeds by decreasing oxidative stress due to drought stress.